Geochemistry of marine sediments adjacent to the Los Tuxtlas Volcanic Complex, Gulf of Mexico: Constraints on weathering and provenance - Armstrong-Altrin, John S.; Ramos-Vázquez, Mayla A.; Madhavaraju, Jayagopal; Marca-Castillo, Mario Emilio; Machain-Castillo, María Luisa; Márquez-García, Antonio Zoilo (Applied geochemistry, 2022)
The provenance of GoM45 and GoM63 core sediments recovered in the deep-sea area (∼1666 m–1672 m water depth, respectively), in front of the Los Tuxtlas volcanic field, Gulf of Mexico was analyzed based on the textural, mineralogical, and geochemical variations. The radiocarbon age data of Globorotalia menardii group foraminiferal species varied from 17,709 to 20,711 calibrated years B.P for the sediment core GoM45, which represent Pleistocene/Holocene boundary. The core sediments were characterized by detrital components with enriched SiO2, Al2O3, and Fe2O3 concentrations. The weathering indices like Chemical Index of Alteration (CIA), Chemical Index of Weathering (CIW), and Plagioclase Index of Alteration (PIA) revealed a low intensity of weathering for the core sediments. The V/Cr, Ni/Co, Cu/Zn, and V/Cr elemental ratios indicated an oxic depositional environment for the Gulf of Mexico deep sea area. In addition, the geochemistry data indicated a passive margin setting, which is consistent with the geology of the Gulf of Mexico. The trace and rare earth element concentrations, and Eu anomaly indicated that the sediments were derived from the natural erosion of andesitic and basaltic rocks in the Los Tuxtlas region, SW Gulf of Mexico. Los Tuxtlas region is partly influenced by the Papaloapan and Coatzacoalcos Rivers, which discharges into the SW Gulf of Mexico. •Provenance of deep-sea sediment cores in the Gulf of Mexico was investigated.•14C ages of Globorotalia menardii indicated ∼17,709 - 20,711 cal yrs BP.•Sediments were derived from the natural erosion of andesitic and basaltic rocks.•Geochemical composition of sediments indicated a passive margin setting.